Respons Tanaman Jahe Merah (Zingiber Officinale) Terhadap Ekstrak Bawang Merah dan Pupuk Hayati Trichoderma - Sutarman Sutarman (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2019)
This study aims to determine the vegetative growth response of saplings of red ginger (Zingiber officinale) to the administration of red onion extract and Trichoderma biological fertilizer. Experiments were arranged factorially using a completely randomized design (CRD). The first factor is the concentration of red onion extract which consists of three levels, namely: 0 gr, 125 gr, and 250 gr per liter of shallot extract; the second factor is Trichoderma biological fertilizer, consisting of: without biological fertilizer and with Trichoderma biological fertilizer. Each combination of treatments was repeated 4 times, to obtain 24 experimental units. The variables observed were plant height (cm), number of leaves, increase in stem diameter (cm), stover wet weight (gr), and dry stover weight (gr) at 24-60 days after planting (DAP). Data were analyzed by variance at the level of 5% to determine the effect of treatment, to find out the differences between treatments were carried out by 5% HSD. The results showed that there was a significant interaction effect between red onion extract and Trichoderma biofertilizer on the increase of high growth of red ginger tillers at 36 and 48 DAP. Both factors and their interactions were not significant for the number of leaves, stem diameter, wet weight, and dry stover weight. The treatment of 125 gr/l shallot extract and Trichoderma biofertilizer produced the highest response of the number of leaves and stem diameter at 60 DAP.